2014
DOI: 10.1108/jcm-06-2013-0603
|View full text |Cite
|
Sign up to set email alerts
|

Promotion and shoppers' impulse purchases: the example of clothes

Abstract: Purpose – This paper draws attention to the fact that impulse buying is common behaviour among modern shoppers and that a consumer's impulse purchases of items such as clothes may be a result of the retailers' promotional activities. The purpose of this paper is therefore to investigate how promotion through channels such as direct-mail marketing, TV commercials and special in-store displays affects consumers' impulse purchases of clothes. Design/method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 43 publications
4
20
0
Order By: Relevance
“…Finally, the promotional variable (X3) gives sig value by 0.000, which is smaller than <0.05 indicating there is partially significant influence between promotion to purchase decision. a consumer responds to promotion through to the intention to buy [32].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the promotional variable (X3) gives sig value by 0.000, which is smaller than <0.05 indicating there is partially significant influence between promotion to purchase decision. a consumer responds to promotion through to the intention to buy [32].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the good SRSQ scenario, the salesperson greeted the customer with a warm smile and friendly gesture, was attentive, anticipated the customer's needs, and maintained a decent communication style. The product category of clothes was chosen because it has been a frequently studied product category (Hultén and Vanyushyn, 2014; Pentecost and Andrews, 2010) and because interviews with 10 adults of the same characteristics as the actual sample indicated that clothes were commonly bought on impulse, consistent with the results in Consumer Reports (2009).…”
Section: Methodsmentioning
confidence: 96%
“…Low pricing resulted in higher purchases of optional products (Karbasivar & Yarahmadi, 2011). One of the promotional strategies is price negotiation for the promotion of market and product purchases, which motivated customers for more buying (Hultén & Vanyushyn, 2014). Generally, all the services and products for the consumers used sales promotion techniques e.g.…”
Section: Unexpected Cheaper Pricementioning
confidence: 99%
“…Meanwhile, those who do purchases on their partial choices they may feel less guilt and some sort of happiness after purchasing (Chen, 2005). Hultén and Vanyushyn (2014) highlighted that consumers usually feel gratification after getting the product impulsively. Significance of the Study Now a day due to the dual and contradictory actions of consumers in buying and though processing for attaining their desirable products, impulse buying now a day grabbed the attention of wide-spread scholars.…”
Section: Introduction Backgroundmentioning
confidence: 99%